Application of Fe(II)/peroxymonosulfate for improving ultrafiltration membrane performance in surface water treatment: Comparison with coagulation and ozonation. (1st November 2017) - Cheng, Xiaoxiang; Liang, Heng; Ding, An; Zhu, Xuewu; Tang, Xiaobin; Gan, Zhendong; Xing, Jiajian; Wu, Daoji; Li, Guibai
Abstract: Coagulation and ozonation have been widely used as pretreatments for ultrafiltration (UF) membrane in drinking water treatment. While beneficial, coagulation or ozonation alone is unable to both efficiently control membrane fouling and product water quality in many cases. Thus, in this study an emerging alternative of ferrous iron/peroxymonosulfate (Fe(II)/PMS), which can act as both an oxidant and a coagulant was employed prior to UF for treatment of natural surface water, and compared with conventional coagulation and ozonation. The results showed that the Fe(II)/PMS-UF system exhibited the best performance for dissolved organic carbon removal, likely due to the dual functions of coagulation and oxidation in the single process. The fluorescent and UV-absorbing organic components were more susceptible to ozonation than Fe(II)/PMS treatment. Fe(II)/PMS and ozonation pretreatments significantly increased the removal efficiency of atrazine, p -chloronitrobenzene and sulfamethazine by 12–76% and 50–94%, respectively, whereas coagulation exerted a minor influence. The Fe(II)/PMS pretreatment also showed the best performance for the reduction of both reversible and irreversible membrane fouling, and the performance was hardly affected by membrane pore size and surface hydrophobicity. In addition, the characterization of hydraulic irreversible organic foulants confirmed its effectiveness. These results demonstrate the potential advantages of applying Fe(II)/PMS as a pretreatment for UF to simultaneously control membrane fouling and improve the permeate quality. Graphical abstract: Highlights: Fe(II)/PMS was applied prior to UF membrane for treating natural surface water. The interaction between Fe(II) and PMS promoted generation of Fe(III) and SO4 − . Fe(II)/PMS significantly improved the removal efficiency of micropollutants for UF. Fe(II)/PMS reduced membrane fouling more efficiently than coagulation and ozonation.